Use of Magnesium Sulphate in Persistent Pulmonary Hypertension of Newborn (Northern International Medical College Journal, 2020)
Background: One of the common causes of respiratory distress in neonate is persistent pulmonary hypertension of newborn (PPHN) and has been estimated to occur in 2 per 1000 live born term infants.Objective: To evaluate the effect of injectable Magnesium Sulphate (MgSO4) in the treatment of Persistent Pulmonary Hypertension of Newborn.Methodology: It was a prospective, nonrandomized, clinical study conducted from August 2015 to July 2017 among 25 neonates having moderate to severe PPHN in the Pediatric Cardiac Intensive Care Unit (CICU) of Dhaka Shishu (Children) Hospital. Injectable Magnesium Sulphate was used along with other supportive management. Outcome measures include drop of pulmonary vascular resistance and increase oxygenation. Side effects of Magnesium Sulphate were observed and outcome was recorded. Data were analyzed by using SPSS version 17.Results: There was significant improvement of oxygenation and decrease in pulmonary vascular resistance at 72 hours after use of MgSO4 (p=000). Complications were present in 28% cases which include hypotension in 16% patients, urinary retention in 8% and altered GI function in 8% cases. Mortality was 16% among study population.Conclusion: MgSO4 is effective in improving oxygenation and reduction of pulmonary vascular resistance in PPHNNorthern International Medical College Journal Vol.10 (2) Jan 2019: 370-372